How we treat medulloblastoma in adults - Franceschi, Enrico; Seidel, C.; Sahm, Felix; Pajtler, Kristian Wilfried; Hau, P. (ESMO open, 2021)
Medulloblastoma is a rare tumour in postpubertal patients and adults that is potentially curable. Several subgroups have been defined that are associated with clinical features, have different prognoses, and in some cases offer personalized treatment options. In adults, the sonic hedgehog (SHH) subtype is the most common subtype, followed by the wingless (WNT) and group 4 subtypes. Multimodal therapies allow 5-year overall survival rates of up to 70%. However, in adults, therapeutic evidence from prospective randomized trials is largely lacking. Therefore, regardless of individual risk, most patients are currently treated uniformly with craniospinal chemoradiation with a boost to the tumour bed, followed by maintenance chemotherapy, usually with alkylating agents. In Europe, the so-called Packer regimen, together with cisplatin-etoposide regimens, is the most commonly used chemotherapy option. Targeted treatment approaches have not yet been implemented, although tumour biology is well understood and offers personalized approaches, especially for the SHH subgroup. At relapse, rapid resistance occurs frequently, necessitating repositioning of these agents in an earlier treatment phase. Due to the good to intermediate prognosis, patients with medulloblastoma require structured long-term clinical follow-up including MRI of the brain, monitoring of side effects, and psychosocial and fertility counselling. Recently, clinical trials have been initiated with the aim of de-escalating treatment to reduce toxicity and adding targeted therapies to increase efficacy, with the main goal of therapy to cure the tumour while maintaining the physical and psychosocial integrity of affected patients. This article summarizes our opinion on the diagnosis and treatment of medulloblastoma in adults.